2021
DOI: 10.1111/gwmr.12485
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Current Approaches for Predicting Groundwater Vulnerability from PFAS Contamination in the Vadose Zone

Abstract: This column reviews the general features of PHT3D Version 2, a reactive multicomponent transport model that couples the geochemical modeling software PHREEQC-2 (Parkhurst and Appelo 1999) with three-dimensional groundwater flow and transport simulators MODFLOW-2000 and MT3DMS (Zheng and Wang 1999). The original version of PHT3D was developed by Henning Prommer and Version 2 by Henning Prommer and Vincent Post (Prommer and Post 2010). More detailed information about PHT3D is available at the website http://www.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Complete retention ( M R = 100%) was a rare exception, even for those that had eight fluorinated carbons (Figure ). Overall, the retention of anionic C ≤ 7 PFAS did not correlate with the OC content in any of the four soil columns (Figure ), indicating that, in low OC systems at least, OC content is not predictive for PFAS retention. , , …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Complete retention ( M R = 100%) was a rare exception, even for those that had eight fluorinated carbons (Figure ). Overall, the retention of anionic C ≤ 7 PFAS did not correlate with the OC content in any of the four soil columns (Figure ), indicating that, in low OC systems at least, OC content is not predictive for PFAS retention. , , …”
Section: Resultsmentioning
confidence: 92%
“…Overall, the retention of anionic C ≤ 7 PFAS did not correlate with the OC content in any of the four soil columns (Figure 3), indicating that, in low OC systems at least, OC content is not predictive for PFAS retention. 22,[28][29][30]32 In the case of zwitterionic PFAS, complete retention (M R = 100%) was the norm (Figure 3) with a minority of zwitterionic PFAS breaking through (M R < 100%) after five pore volumes of water. The spread in M R was greatest for C ≤ 4 zwitterionic PFAS.…”
Section: Retention Of Molecular Cohorts Of Pfas As a Function Of Equi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive application of aqueous film-forming foams (AFFF) containing per- and polyfluoroalkyl substances (PFAS) for extinguishing hydrocarbon-based fires, along with other surfactants and solvents, has led to their widespread distribution in a variety of environmental media. AFFF solutions can infiltrate into the vadose zone and become a major reservoir for PFAS release and thus serve as a long-term source of groundwater contamination. PFAS-contaminated aquifers that also serve as a drinking water source can result in a primary PFAS exposure route for humans. …”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, contaminant occurrence in groundwater is predicted using mechanistic models based on physicochemical properties of the contaminant and aquifer. , However, building such models to predict PFOA fate and transport is challenged by the wide variety of potential sources, complex chemical mixtures typically present in those sources, potential for pollutant cotransport, and lack of accurate parameters describing related physicochemical processes (such as sorption at fluid-water and solid–water interfaces) in real-world and highly heterogeneous subsurface media . For example, a recent case study evaluation of a mechanistic model for predicting PFOA occurrence in Michigan’s Huron River watershed concluded that the model “underestimated the magnitude of PFOA concentration due to a lack of information from diffusive sources and historical loads” …”
Section: Introductionmentioning
confidence: 99%